2013
DOI: 10.1093/cid/cit610
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Diseases Specialty Intervention Is Associated With Decreased Mortality and Lower Healthcare Costs

Abstract: ID interventions are associated with improved patient outcomes. Early ID interventions are also associated with reduced costs for Medicare beneficiaries with select infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
102
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(112 citation statements)
references
References 17 publications
5
102
0
5
Order By: Relevance
“…An ID physician-and pharmacist-led ASP provides key experience and clinical knowledge along with access to formal ID consultation, which is known to improve clinical outcomes [27]. However, a common barrier small hospitals face is a lack of dedicated ID-trained staff to support the ASP.…”
Section: Infectious Diseases Physician and Pharmacy Leadershipmentioning
confidence: 99%
“…An ID physician-and pharmacist-led ASP provides key experience and clinical knowledge along with access to formal ID consultation, which is known to improve clinical outcomes [27]. However, a common barrier small hospitals face is a lack of dedicated ID-trained staff to support the ASP.…”
Section: Infectious Diseases Physician and Pharmacy Leadershipmentioning
confidence: 99%
“…Maeda et al [4] showed that an AST intervention approach decreases the use of inappropriate therapy and may improve clinical outcomes in BSI patients and previous other studies have reported that clinical intervention by infectious disease specialists also reduces mortality, length of stay (LOS) and medical costs. These results indicate that ICT/AST interventions can decrease inappropriate therapy and also potentially improve clinical and economic outcomes in severe infectious disease, including pneumonia and BSI by P aeruginosa [9,10].…”
Section: Introductionmentioning
confidence: 84%
“…Estos resultados son semejantes a los obtenidos por otros autores tanto a nivel internacional como nacional [22][23][24][25][26] .…”
Section: Asociación Colombiana De Infectologíaunclassified
“…Dado que no podemos influir en las comorbilidades que el paciente presenta, ni en su gravedad en la presentación, es responsabilidad de los clínicos y del sistema sanitario 7,8,[23][24][25][26] contribuir a la mejora en la calidad asistencial de los pacientes con bacteriemia mediante políticas de control y uso adecuado de antibióticos y mediante la valoración del consultor en Patología Infecciosa de dichos pacientes. …”
Section: Asociación Colombiana De Infectologíaunclassified